Investigating the Effect of Adhan on Anxiety and Pain Level in Patients after Cesarean Operation by Spinal Anesthesia: A Prospective Clinical Trial Study - Zahra Naeiji; Khadijeh Lorestani; Ahmadreza Baghestani (Shahid Beheshti University of Medical Sciences, 2020)
For downloading the full-text of this article please click here. Background and Objective: Severe pain and post-surgical anxiety cause unpleasant psychological and physical complications. Today, the common method used for relieving pain and anxiety is the use of medication. However, due to the side effects associated with anesthetics, there is a greater desire for a non-drug method including music therapy. The aim of the present study was to investigate the effect of Adhan on anxiety and pain in patients undergoing caesarean section by spinal anesthesia. Methods: In a clinical trial study, 64 women, who were candidates for caesarean section in Mahdieh hospital in Tehran from 2016 to 2017, were selected for the purpose of the study by random sampling method and assigned to two groups of 32, one as the experimental and the other as the control group. Adhan was played for one group but not for the control group. Data were collected using a questionnaire and pain visual analogue. The collected data were analyzed using independent samples t-test. In this study, the value (P<0.05) was considered statistically significant. In this study, all the ethical considerations have been observed and no conflict of interest was reported by the authors. Results: One hour after operation, the mean score related to anxiety was found to be significantly lower in the experimental group than the control group (P<0.001). Pain mean score in the baseline time was not significantly different (P=0.20), but 15 minutes (P<0.001), 30 minutes (P=0.006) and 60 minutes (P=0.04) after the operation it was significantly lower in the experimental group than the control group. Conclusion: In the present study, the tone of Adhan could efficiently decrease anxiety and pain. For downloading the full-text of this article please click here. Please cite this article as: Naeiji Z, Lorestani Kh, Baghestani AR. Investigating the Effect of Adhan on Anxiety and Pain Level in Patients after Cesarean Operation by Spinal Anesthesia: A Prospective Clinical Trial Study. Journal of Pizhūhish dar dīn va salāmat. 2020;6(2):7-19.  https://doi.org/10.22037/jrrh.v6i2.23471